Regulatory Reform and Productivity Change in Indian Banking - Casu, Barbara; Ferrari, Alessandra; Zhao, Tianshu (The Review of Economics and Statistics, 2013)
This paper examines the impact of regulatory reform on productivity growth and its components for Indian banks from 1992 to 2009. We estimate parametric and nonparametric efficiency frontiers, followed by Divisia and Malmquist indexes of total factor productivity, respectively. To account for technology heterogeneity among ownership types, we use a metafrontier approach. Results are consistent across methodologies and show sustained productivity growth, driven mainly by technological progress. Furthermore, results indicate that different ownership types react differently to changes in the operating environment. The position of foreign banks becomes increasingly dominant, and their production technology becomes the best practice in the industry.